Assessment of knowledge, perception and attitude towards antibiotic resistance among medical interns in Saudi Arabia - Albarrag, Ahmed; Almeshari, Nawaf Zaid; Alfraih, Abdullah Ameen; Alshathry, Abdullah Hassan; Alzaydan, Abdulaziz Mohammed; Benaskar, Abdulrahman Mansour; Aleidy, Abdullah Mohammed; Alzahrani, Khaloud (International Journal Of Community Medicine And Public Health, 2021)
Background: Antibiotic resistance is a well-established medical fact that affects the clinical course of many infections. There are many risk factors that can contribute to antibiotic resistance clinically. Therefore, it is important to understand the attitude and practice of medical practitioners from their early life career. Methods: This is a cross-sectional descriptive online study that was done between February and March 2018 in Riyadh, Saudi Arabia. The included participants were medical interns only excluding all other medical students. The questionnaire is made up of four dimensions: Socio-demographic characteristics, antibiotics knowledge, attitude, and perception towards prescribing antibiotics. The questionnaire utilized from a previously validated questionnaire regarding antibiotic use, and the data was analyzed using SPSS, version 21. Results: A total of 292 medical interns completed the questionnaire. Majority of Interns reported that too many antibiotic prescriptions were important contributor to antibiotic resistance. Surprisingly, 55.6% felt that hand hygiene had low importance or was not important at all in compacting antibiotic resistance. Only half of respondents (51%) were sure that their hospitals had antibiotic guidelines, and only 21% of them had acknowledged reading the guidelines or been shown where the hospital’s antibiotic guidelines were kept. The majority of the interns (90.6%) believed that antibiotic resistance is a national problem in Saudi Arabia. Conclusions: There is a noticeable gap between the theoretical part of students’ curricula and clinical practice; students require more education regarding antibiotic prescription, especially about choosing the correct antibiotics, doses, and intervals.